How Biofeedback With Surface EMG Can Contribute to the Diagnosis and Treatment of AMI in the Knee - Thomas Richaud MD; Kevin Lacaze PT; Alexandre Fassio PT; Paul Nicolas PT; Maxime Ourliac PT; Benoit Hennart PT; Jason G. Ina MD; Bertrand Sonnery-Cottet MD, PhD; Etienne Cavaignac MD, PhD (SAGE Publishing, 2024)
Background: Arthrogenic muscle inhibition (AMI) is a complex neurological phenomenon that is actually very common. AMI can appear following a knee injury or knee surgery. If it is not addressed, the patient's function can be negatively affected. There is currently no specific tool for the diagnosis and treatment of AMI. Indications: Following surgery or injury to the knee, AMI causes defective activation of the quadriceps, sometimes combined with a knee extension deficit. A clinical classification of AMI has been proposed recently to help with making the diagnosis and to guide treatment. In this article, we describe how biofeedback and surface electromyography (EMG) can be used in the early diagnosis and treatment of knee AMI. Technique Description: Biofeedback is based on transformation of physiological variables into a visual or auditory signal. This allows the patient to learn how to control physical and bodily functions, which were previously considered as involuntary processes. This technique requires the use of a specific device that transforms the measured physiological signals-neuromuscular activation in this instance-into visual signals. This tool incorporates surface EMG, with electrodes connected to a measuring unit. This unit is connected to a screen that shows the neuromuscular activation in real time. Thus, EMG biofeedback can be used to help clinicians make a diagnosis and to specifically treat the AMI. Results: We have used biofeedback in patients who have a knee injury or who have undergone knee surgery. Both the therapist and patient were able to objectively see the presence of AMI using the biofeedback device. For treatment, the therapist works with a patient by providing clear instructions and increasingly more challenging goals. We show examples of how patients were able to eliminate their AMI by using biofeedback. Discussion/Conclusion: EMG biofeedback is a promising tool for the diagnosis and treatment of AMI after an anterior cruciate ligament (ACL) tear and ACL reconstruction surgery. The next steps are to define thresholds and a rehabilitation protocol that will be used in a clinical trial. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.